2015
DOI: 10.1159/000381867
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Diverticulosis, Diverticulitis, Diverticular Perforation, and Bleeding: A Plea for More Subtle History Taking

Abstract: Background: Diverticulosis is a very common condition. Around 20% of diverticula carriers are believed to suffer from diverticular disease during their lifetime. This makes diverticular disease one of the clinically and economically most significant conditions in gastroenterology. The etiopathogenesis of diverticulosis and diverticular disease is not well understood. Epidemiological studies allowed to define risk factors for the development of diverticulosis and the different disease entities associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 124 publications
(234 reference statements)
4
48
0
1
Order By: Relevance
“…Other studies have also observed that African Americans and Japanese immigrants in western countries developed diverticular disease at similar rates as native westerners. 17,20 In a cohort study that looked at more than 47,000 men, total dietary fiber intake was noted to be inversely associated with risk of symptomatic diverticular disease (relative risk [RR] ¼ 0.58). 21 On the contrary, other studies have shown either no effect of dietary fiber intake or an even positive correlation between fiber intake and diverticulosis.…”
Section: Lack Of Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also observed that African Americans and Japanese immigrants in western countries developed diverticular disease at similar rates as native westerners. 17,20 In a cohort study that looked at more than 47,000 men, total dietary fiber intake was noted to be inversely associated with risk of symptomatic diverticular disease (relative risk [RR] ¼ 0.58). 21 On the contrary, other studies have shown either no effect of dietary fiber intake or an even positive correlation between fiber intake and diverticulosis.…”
Section: Lack Of Fibermentioning
confidence: 99%
“…For the time being, there is a consensus in the presence of significant benefit that is obtained from fiber for overall health of patients and should continue to be recommended as part of daily diet. 20 The Dietary Reference Intakes recommends consumption of 14 g of dietary fiber per 1,000 kcal of diet, or 25 g for adult women and 38 g for adult men.…”
Section: Lack Of Fibermentioning
confidence: 99%
“…Diverticular disease is the symptomatic manifestation (normally abdominal pain) of people who have developed diverticula, which are small bulges in the large intestine 31 . Approximately one in every four people with it will develop diverticulitis, which is the inflammation caused by bacteria and is associated with increased risk of intestinal perforation 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Diverticular disease is the symptomatic manifestation (normally abdominal pain) of people who have develop diverticula, which are small bulges in the large intestine (31). Approximately 1 every 4 people with will develop diverticulitis, which is the inflammation lead by bacteria and is associated with increased risk of intestinal perforation (32).…”
Section: Introductionmentioning
confidence: 99%